UPAYA MENINGKATKAN MINAT DAN PRESTASI BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN COOPERATIVE TIPE TEAMS GAMES TOURNAMENT (TGT) PADA SISWA KELAS IV SDN 1 TEMUWANGI PEDAN KLATEN - Awang Sunaryo; AA Sujadi (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2016)
The purpose of this study was to describe the process of learning Cooperative type Teams Games Tournament (TGT) in order to increase interest and learning mathematics achievement in grade IV Elementary School 1 Temuwangi Pedan Klaten. This study uses a classroom action research conducted in two cycles. Data obtained from the results of observations, questionnaires and tests. The results showed that the application of cooperative learning model type Teams Games Tournament (TGT) may increase the interest and learning achievement at the fourth grade students of State Elementary School 1 Temuwangi Pedan Klaten. This is evidenced by the average percentage of student interest in the pre-action based observation data obtained by 24,38% increased to 65% in the first cycle and increased again to 83,75% in the second cycle. Also based on a questionnaire obtained an interest in the first cycle an average of 84,17%. Then on the second cycle increased to 88,33%. Student achievement also increased with an average value of 54,5 pratindakan increased to 69,69 in the first cycle and then increased to 74,438 in the second cycle. In conclusion Cooperative models of type Teams Games Tournament (TGT) may increase the interest and learning achievement at the fourth grade students of State Elementary School 1 Temuwangi Pedan Klaten.